Linguagens entrecruzadas num espaço modulado ou neobarroco em A fuga para o Egipto, Gémeo e Amadeo, de Mário Cláudio - Sousa, Lúcia Melo de (2013)
This paper aims to develop an analysis of one novel and two romances written by Mário Cláudio: A Fuga para o Egipto, Gémeos and Amadeo, respectively, all based on a plan of writing that belongs to a modulated biographic textual space an space that represents more than a mere intertextuality with the biographic genre, but that makes use of it as a style, a fictional project. The present analysis brings to focus a dialog with arts as well as profitable questions about the frontiers of biography, self-biography, novel and critical essays on art. In bringing the frontiers of genre into question, Mário Cláudio s texts foster a permanent movement of form and style because, once they are rough and ambiguous, they promote entertainment on the text contents by the means of formal entertainment. Thus, when Mario Claudio s writing takes form on a biographical space it resembles the present contemporary cultural forms that some critics as Severo Sardut and Omar Calabrese called neo-baroque. Through this modulated form the author writes in a way where we can find two distinct movements: the creative one and the critical one. There is no doubt that Marioclaudianos texts will be of great help for the esthetic studies as, for instance, the study that concerns the value of the artistic object as well as of the artists in general.